2010
DOI: 10.3168/jds.2009-2799
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the fatty acid composition of retail milk differing in label claims based on production management practices

Abstract: Consumers are becoming increasingly health conscious, and food product choices have expanded. Choices in the dairy case include fluid milk labeled according to production management practices. Such labeling practices may be misunderstood and perceived by consumers to reflect differences in the quality or nutritional content of milk. Our objective was to investigate nutritional differences in specialty labeled milk, specifically to compare the fatty acid (FA) composition of conventional milk with milk labeled a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 38 publications
7
49
1
Order By: Relevance
“…PC1 consisted of the typical FA that can be found in the milk of small ruminants (C8:0 and C10:0) (Partidário et al, 2008) whereas C14:1c9 and C16:1c9 are usually detected in the milk and cheeses of cows (O'Donnell et al, 2010). Figure 1 shows a clear difference among animal species particularly between Groups I and II.…”
Section: Multivariate Analysismentioning
confidence: 99%
“…PC1 consisted of the typical FA that can be found in the milk of small ruminants (C8:0 and C10:0) (Partidário et al, 2008) whereas C14:1c9 and C16:1c9 are usually detected in the milk and cheeses of cows (O'Donnell et al, 2010). Figure 1 shows a clear difference among animal species particularly between Groups I and II.…”
Section: Multivariate Analysismentioning
confidence: 99%
“…The lower milk yield of these cows had a positive impact on the higher level of vitamins A, E, and D 3 as well as on the beneficial fatty acids content compared to the conventional group. Butler et al (2009Butler et al ( , 2011a, Prandini et al (2009), O'Donnell et al (2010, and Popović- Vranješ et al (2011) show the positive effect of organic farming residing in increasing the content of n-3 PUFA (as a-linolenic acid), CLA, vitamin A, and antioxidants (a-tocopherol, lutein, zeaxanthin, and β-carotene) in milk; substances that are generally considered beneficial to health (Halliwell 1996;McGuire & McGuire 1999;Lemaitre et al 2003).…”
mentioning
confidence: 99%
“…However, previous studies found that, compared to grazing (Elgersma, 2015) or organic farming conditions (O'Donnell et al, 2010), partial feeding of housed dairy cows with fresh forage had only a limited effect on the proportion of nutritionally desirable FA in milk fat (Leiber et al, 2005). This could explain the low level of variation in oleic acid (6 %) and the group of monounsaturated FA (5 %).…”
Section: Resultsmentioning
confidence: 93%